Corrosion mitigation of J55 steel in 3.5% NaCl solution by a macrocyclic inhibitor - Singh A.; Lin Y.; Obot I.B.; Ebenso E.E.; Ansari K.R.; Quraishi M.A. (My University, 2025)
1,2,4,7,9,10-Hexaazacyclo-pentadeca-10,15-dien-3,5,6,8-tetraone (HPT) a macrocyclic compound has been studied using electrochemical methods and scanning electrochemical microscopy (SECM) techniques. The R ct values increased and C dl values decreased with the increase in concentration of the inhibitor. The corrosion inhibition of J55 steel in 3.5 wt.% NaCl solution saturated with CO 2 by polarization studies revealed that HPT acted as a mixed type inhibitor. The adsorption of HPT on the J55 steel surface obeyed the Langmuir adsorption isotherm. The thermodynamic parameters (K ads , ΔG° ads ) were also computed and discussed. © 2015 Elsevier B.V. All rights reserved.